Factors Influencing Mathematics Achievement Among Secondary Students in Nepal: Evidence from Hierarchical Regression Analysis - Manandhar, Dev Chandra (International Research Journal of MMC, 2026)
Secondary-level mathematics achievement is vital for students’ academic growth and future science, technology, engineering and mathematics (STEM) opportunities. However, many students in developing countries still perform poorly in mathematics. This study aims to investigate the key factors influencing mathematics achievement among secondary school students in Nepal. A quantitative survey research design was conducted with 206 Grade 9 and 10 students from six urban and rural public schools in Makwanpur district in 2025. Data were collected via a structured questionnaire on learning factors and students’ mathematics scores from school records. SPSS was used for descriptive statistics, correlation, and regression analyses to determine each factor’s impact on achievement. The findings reveal that student-related factors, particularly self-efficacy, motivation and study habits, are the strongest predictors of mathematics achievement (β = 0.497, p < .001). School-related factors and parental or socioeconomic support also demonstrate significant positive contributions, while teacher-related variables do not show a significant independent effect when other variables are controlled. A moderate but significant achievement gap between urban and rural students was found. The study emphasizes improving student motivation, learning strategies, and educational resources—especially in rural schools—to enhance mathematics achievement and reduce disparities.